Analisis Kerawanan Longsor Menggunakan metode CMA di Kabupaten Tana Toraja : Landslide Vulnerability Analysis Using CMA Method in Tana Toraja Regency - Roihan, Afdalul; Mataburu, Ilham Badaruddin (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2025)
Tana Toraja Regency has geographical characteristics that are prone to landslides due to its hilly topography and high rainfall. This study aims to analyze the level of landslide vulnerability using Composite Mapping Analysis (CMA) method by integrating six parameters: rainfall, slope, land use, elevation, soil type, and geology. The analysis results show that the geological factor has the highest weight (36.95%), followed by slope (26.44%), and rainfall (18.17%). Based on the vulnerability zoning, 83.54% of the area is categorized as safe, 9.51% is not vulnerable, 2.18% is vulnerable, and 4.77% is highly vulnerable. Highly vulnerable areas are concentrated in the southern and eastern parts of the district, especially in areas with a combination of high rainfall, steep slopes and unstable geology. This study produced a landslide vulnerability zonation map that can be used as a reference in disaster mitigation planning and spatial planning of Tana Toraja Regency.